Publicações de relatórios de sustentabilidade nas cooperativas brasileiras segundo as diretrizes gri. - Souza, Maria Rosiane de (Universidade Federal do Tocantins, 2023)
The research deals with the publication of sustainability reports in Brazilian cooperatives, bringing a survey of cooperatives that disseminate sustainability reporting in accordance with the guidelines of the pioneering organization in sustainability reporting, the Global Reporting Initiative (GRI), we sought to examine the version of guidelines used in each of the reports with GRI G3 GRI 3.1 GRI G4 or with external verification and are certified by the GRI. What about the reports published outside these guidelines in which these key aspects do not meet the wide dissemination of the information proposed by the Global Reporting Initiative, for this analysis we tried to research the Brazilian cooperatives, their websites and published sustainability reports. According to the survey, the publication of sustainability reports in cooperatives is a little-used practice, which fails to meet the principle of cooperative governance transparency in which these organizations need to be transparent in order to allow its members make efficient decisions through information made available and the report not only covers information for associates, it is a management tool that meets all the public interest, and may also be society, major users of information, according to the principle of inclusion stakeholders. To answer some questions such as the reasons why these organizations correspond such a small percentage of publishing sustainability reports in Brazil, only health insurance lines, credit and agricultural publications that had, are necessary further research.